STRENGTH AND STABILITY OF TWO-LAYER COMBINED CONCRETE/GLASS-FIBRE REINFORCED CONCRETE SLABS CONSIDERING TRANSVERSE SHEAR AND ADHESIVE JOINT PLIABILITY - Dusmatov A. D.; NabievaS.X. (Journals Park Publishing, 2024)
The strength and stability of two-layer combined concrete and glass-fibre-reinforced plastic slabs are investigated in this paper, taking into account transverse shear and ductility of the adhesive joint. The influence of interlayer shear on the stability of two-layer combined concrete and fibreglass slabs has been investigated.
Keywords: Two-layer slab, reinforcing composite layer, shear modulus, shear function, tangential stress, displacements, shear modulus of layers and glue joints.